Counseling Received by Adolescents Undergoing Voluntary Medical Male Circumcision: Moving Toward Age-Equitable Comprehensive Human Immunodeficiency Virus Prevention Measures. (3rd April 2018) - Kaufman, Michelle R; Patel, Eshan U; Dam, Kim H; Packman, Zoe R; Van Lith, Lynn M; Hatzold, Karin; Marcell, Arik V; Mavhu, Webster; Kahabuka, Catherine; Mahlasela, Lusanda; Njeuhmeli, Emmanuel; Seifert Ahanda, Kim; et al.
Abstract: Background: The minimum package of voluntary medical male circumcision (VMMC) services, as defined by the World Health Organization, includes human immunodeficiency virus (HIV) testing, HIV prevention counseling, screening/treatment for sexually transmitted infections, condom promotion, and the VMMC procedure. The current study aimed to assess whether adolescents received these key elements. Methods: Quantitative surveys were conducted among male adolescents aged 10–19 years (n = 1293) seeking VMMC in South Africa, Tanzania, and Zimbabwe. We used a summative index score of 8 self-reported binary items to measure receipt of important elements of the World Health Organization–recommended HIV minimum package and the US President's Emergency Plan for AIDS Relief VMMC recommendations. Counseling sessions were observed for a subset of adolescents (n = 44). To evaluate factors associated with counseling content, we used Poisson regression models with generalized estimating equations and robust variance estimation. Results: Although counseling included VMMC benefits, little attention was paid to risks, including how to identify complications, what to do if they arise, and why avoiding sex and masturbation could prevent complications. Overall, older adolescents (aged 15–19 years) reported receiving more items in the recommended minimum package than younger adolescents (aged 10–14 years; adjusted β, 0.17; 95% confidence interval [CI], .12–.21; P < .001). Older adolescents were also more likely to report receiving HIV test education and promotion (42.7% vs 29.5%; adjusted prevalence ratio [aPR], 1.53; 95% CI, 1.16–2.02) and a condom demonstration with condoms to take home (16.8% vs 4.4%; aPR, 2.44; 95% CI, 1.30–4.58). No significant age differences appeared in reports of explanations of VMMC risks and benefits or uptake of HIV testing. These self-reported findings were confirmed during counseling observations. Conclusions: Moving toward age-equitable HIV prevention services during adolescent VMMC likely requires standardizing counseling content, as there are significant age differences in HIV prevention content received by adolescents.